The Use of Brainstorming Technique in Increasing Student Confidence in English Speaking Skills at SMAN 4 Kota Serang - Fitriah Fitriah; Ida Nuraida; Lia Amalia (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2022)
The objective of the research to describe and analyze the use of Brainstorming technique in increasing students' confidence in English speaking skills in class X IPS 4 SMAN 4 Kota Serang. In this research, focus on the use of Brainstorming Technique and as sub focuses on improving Self-confidence in English speaking skills the writer. This research uses qualitative research with this type of research method is descriptive. The instrument used voice and video recording devices and cameras from cellphones as well as accurate documents, journal, or books that are considered relevant based on records from various sources, observation and inteview guidelines. Technique of collecting data using three ways, namely interviews, observations and documentation. The data analysis technique is to perform data reduction stages, display data, and conclude data. The results of the analysis are conveyed through the delivery of descriptive data. The results of the study, it can be concluded in general that the Brainstorming technique is considered capable of increasing students' confidence in English speaking skills in class X IPS 4 SMAN 4 Kota Serang in the 2021/2022 school year. Although the effect is not significant when used in distance learning. This can be proven based on the results of research conducted in non-test with the informants. Brainstorming can be used both as a teaching technique and as a teaching strategy. It is very useful for students to develop their reasoning skills, creative problem-solving skills, fluency in English language, self- motivation, and self-confidence